The effects of target-controlled infusion of lidocaine undergoing vocal cord polypectomy: A randomized controlled trial (CONSORT compliant) - Zhou, LongYuan; Wu, RuiLan; Cai, Chang; Qi, Yong; Bi, XingHua; Hang, Qi (Medicine (Baltimore), 2022)
The present study aimed to assess the efficacy and safety of general anesthesia-assisted target-controlled plasma infusion of lidocaine in patients with vocal cord polypectomy using a supporting laryngoscope. In total, 80 patients undergoing vocal cord polypectomy using a supporting laryngoscope were randomly divided into an intervention group and a control group; each group contained 40 subjects: both groups received general anesthesia; subjects in the intervention also received an additional 3 mg/L of lidocaine by target-controlled plasma infusion during induction and maintenance of anesthesia; heart rate (HR) mean arterial pressure (MAP), propofol and urapidil consumption (Uradil, which is a blood pressure drug that blocks alpha-1, is called Urapidi Hydrochloride Injection. It is produced by Germany, the enterprise name is Nycomed Deutschland GmbH, the import drug registration number is H20090715, and it is widely used in China), recovery time, and cough score (measured by Minogue et al's 5-grade scoring method) during extubation, and throat pain score (measured by visual analogue scale,[VAS]) after extubation and adverse events were recorded. Significant differences were observed in HR (P < .05) and MAP (P < .05) immediately after intubation (T2), immediately after the operation starting to support laryngoscope exposure (T3), immediately after operation field adrenergic tampon hemostasis (T4), and 5 minutes after hemostasis (T5) between the 2 groups, and significant differences were also observed in HR (P < .05) before intubation (T1). Moreover, significant differences were observed in propofol consumption (P < .05), urapidil consumption (P < .05), cough score during extubation (P < .05), and throat pain score after extubation (P < .05). However, no significant difference was observed in the recovery time (P > .05). Furthermore, no adverse events were detected in either group. The results of this study showed that target-controlled plasma infusion of lidocaine can reduce propofol consumption in patients undergoing vocal cord polypectomy by supporting laryngoscopy, and the hemodynamics are more stable and reduce the coughing reaction in the wake period and throat pain after extubation without adverse events.